Significant relationships among frost tolerance and net photosynthetic rate, water use efficiency and dehydrin accumulation in cold-treated winter oilseed rapes - Urban, Milan Oldřich (Journal of plant physiology, 2013)
Copyright © 2013 Elsevier GmbH. All rights reserved.